(3JGQjN GdHQjgi (B( (3GdeNJUQ (B)s ((3YHO Gddg Hf TeS GdOjf Hf YHO Gddg GdSdai s)
(3ChdgG (B:s
(3GdMeO ddg GdPi ejR YUGHI GdSfI HCfhGQ Gdjbjf CeG HYO agPG cJGH JGQjN eNJUQ ef GdJGQjN GdcHjQ GdPi LeYJg ai HjGf GdYdeGA hGdaVdGA HGdjef s
(3BNQgG (B:s
(3BNQg ai JQLeI CHj ESMGb EHQGgje Hf fXGe Hf efUhQ (B" (3hef ahGFOg Cfg SFd Yf bhdg Udi Gddg Ydjg hSde ai GdPjf jYPGHf ai bHQjgeG ceG Cf GdfejejI JJYOi ef TNU Zdi TNU bGd ai GdCe GfJgi GdehLhO ef GdJGQjN GdePchQ s
(3JeJ ebGHdJgG Ydi GdCUd Gdefbhdg efg SfI (B1177(3g`s
(3YdjgG Jedc ZjQ eDQN HGSe GdSjO TjN Hf eMeO Hf MSjfs
(3hHYV GdcdeGJ cJHJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs